The challenge of education for sustainability in higher education: key themes and competences within the University of the Basque Country - Idoiaga Mondragon, Nahia; Yarritu, Ion; Saez de Cámara, Estibaliz; Beloki, Nekane; Vozmediano, Laura (Frontiers in Psychology, 2023)
Introduction One of the major challenges for higher education institutions in the last decade has been (and will continue to be) the integration of sustainability into their curricula and the development of sustainability competences in students. Education for Sustainability (ES) can help prepare students to meet the challenges of making societies more sustainable. However, as a first step toward this goal, teachers need to incorporate ES into their teaching. In this regard, this research aimed to analyze if members of the teaching staff have started this integration and, if so, which sustainability-related topics have been introduced and which skills do they consider contribute to the development of future graduates. Methods A questionnaire was administered to teaching staff at the University of the Basque Country in 2022. A total of 403 teachers completed the questionnaire, expressing their perceptions through open-ended questions. Results In general terms teachers incorporate ES into their teaching (71.22%). However, they do this mainly within the framework of two general themes: “Environmental awareness and energy” – most used by teachers of experimental sciences and engineering – and “Social commitment,” most used by teachers of social sciences and those who are familiar with the UN 2030 Agenda for Sustainable Development. Regarding the key competences that ES provides for future graduates, those most frequently mentioned were “training of professionals committed to society” and “critical thinking and ethics.” These competences were particularly notable in the discourse of teachers who were aware of the 2030 Agenda and who use active methodologies in their classrooms. Finally, the opinion that sustainability has little to do with their teaching (28.78%) was notably expressed by teachers less familiar with the 2030 Agenda. Discussion Thus, it can be concluded that, aside from knowledge of the 2030 Agenda, factors such as the sustainability policy of the institution, area of teaching expertise, and the use of active methodologies all play a significant role in determining whether competences for sustainable development are integrated into higher education teaching.